Performance Indices and Physiological Changes in Pearl Guinea Fowls (Numida Meleagris) Supplemented with Molasses through Drinking Water - Habibu, Buhari; Ikira, Nizam Mustapha; Ibrahim, Moses; Buhari, Hajarah Uwale; Abdullahi, Abdullahi; Ibrahim, Muhammed Abdul; Kawu, Mohammed Umar (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
Abstract. The study was aimed at evaluating the performance indices and physiologic changes in pearl guinea fowls (Numida meleagris) supplemented with molasses through drinking water. A total of thirty-two (n=32) day-old pearl guinea fowls raised to 12-week-old were used for the study. The fowls were randomly allocated to two groups (control and experimental) of 16 fowls each, with each having two replicates. Experimental fowls were given 5 mL molasses per litre of drinking water for 8 weeks, while control fowls were given only drinking water. Performance indices which include: feed consumption, water intake and percentage weight gain were measured. Rectal temperature was measured and blood samples were collected to evaluate the changes in haematological parameters, serum triiodothyronine (T3) and thyroxine (T4) concentrations. Â Results revealed that the molasses-treated fowls had significantly (P<0.05) higher percentage weight gain, blood total protein, packed cell volume and mean corpuscular volume compared to control. However, the feed consumptionwas significantly lower (P<0.05) in the molasses-treated fowls compared to control. In both groups, rectal temperature increased significantly (P<0.05) during the afternoon hours and was lower (P<0.05) in molasses-treated fowls than control during the evening hours. There was no significant difference in other haematological parameters, serum glucose, T4 and T3 betweengroups. In conclusion, molasses supplementation decreased feed consumption, improved body weight gain and enhanced nutritional status and erythropoiesis in guinea fowls.